Reaction‐based probe for hydrogen sulfite: dual‐channel and good ratiometric response. (2nd March 2016) - Cheng, Xiaohong; He, Ping; Zhong, Zhicheng; Liang, Guijie
Abstract: We designed and synthesized a new series of intramolecular charge transfer (ICT) molecules (compounds T1, T2 and T3) by attaching various electron‐donating thiophene groups to the triphenylamine backbone with aldehyde group as the electron acceptor. Based on the nucleophilic addition reaction between hydrogen sulfite and aldehyde, all compounds could act as ratiometric optical probe for hydrogen sulfite and displayed efficient chromogenic and fluorogenic signaling. Upon the addition of hydrogen sulfite anions, probe T3 displayed apparent fluorescent color changes from yellowish‐green to blue, with a large emission wavelength shift (Δλ = 120 nm). T3 responded to hydrogen sulfite with high sensitivity and the detection limit was determined to be as low as 0.9 μM. At the same time, apparent changes in UV–vis spectra could also be observed. By virtue of the special nucleophilic addition reaction with aldehyde, T3 displayed high selectivity over other anions. Copyright © 2016 John Wiley & Sons, Ltd.